Development of Matakidi Bath Tourism in the Protected Forest Area of Barangka Village, Barangka District, West Muna Regency - Dewi Fitriani; Sahindomi Bana; Agus Setiawan; Nurhayati Hadjar; Sarwinda Intan Putri; Putriyanti Usman; Pradina Anjarwati Sukirno; Davik (Jurusan Kehutanan -FHIL-UHO, 2025)
Matakidi Bath Tourism is a natural tourism destination located in Barangka Village, Barangka District, West Muna Regency, known for its pristine natural beauty. This study uses SWOT analysis to design a development strategy for the area. The research was conducted through observation, interviews, and surveys distributed at the research location. The respondents included management, local residents, and visitors, selected through purposive sampling. The study results indicate that the tourism area has an attraction score of 95 with a total score of 570 out of a maximum of 720 resulting in a feasibility index of 79.16%. Amenities received a score of 90 with a total score of 270 out of 300 giving it a feasibility index of 90%. Accessibility scored 85, with a total score of 255 out of 360, resulting in a feasibility index of 70.83%. The overall feasibility index of the Matakidi Natural Hot Springs Tourism is 79.99%. Based on the analysis of attraction, amenities, and accessibility, all three criteria are deemed feasible for development. The SWOT analysis suggests developing the full potential of Barangka Village and leveraging local government support for successful growth.